Wiener and Hyper-Wiener Indices of Polygonal Cylinder and Torus - Zhi-Ba Peng; Abdul Rauf Nizami; Zaffar Iqbal; Muhammad Mobeen Munir; Hafiz Muhammad Waqar Ahmed; Jia-Bao Liu (Complexity)
In this study, we first introduce polygonal cylinder and torus using Cartesian products and topologically identifications and then find their Wiener and hyper-Wiener indices using a quick, interesting technique of counting. Our suggested mathematical structures could be of potential interests in representation of computer networks and enhancing lattice hardware security.